Tinjauan Bai' as-sharf Terhadap Legalitas Perdagangan Cryptocurrency di Aplikasi Tokocrypto - Azizah, Andar Nur; Ananggu, Dimas Firmansyah (Fawaid : Sharia Economic Law Review, 2025)
This study aims to examine the legitimacy of cryptocurrency trading activities, particularly Bitcoin, from a bai' as-sharf perspective, using the Tokocrypto trading application. Cryptocurrency is a rapidly growing digital asset widely used in investment and trading activities in the era of financial technology. In Islamic law, a sharf contract must fulfill certain conditions, such as there being a handover between the two parties before separation (taqabudh), an equivalent exchange value, carried out in cash, and free from the right of khiyar and free from elements of speculation (maysir) and uncertainty (gharar). This study is a literature study using content analysis methods. Data were obtained from legal documents, fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), classical and contemporary sources, and official information from Tokocrypto. The results show that most transactions on Tokocrypto use a spot system that takes place directly and openly with conversion to rupiah. However, features such as limit orders, stop-limit orders, and recurring purchases (dollar cost averaging) can contain elements of delay and uncertainty that could potentially violate the principles of bai' as-sharf. So, in general, the activities carried out in the Tokocrypto application contain elements of gharar. Therefore, additional regulations are needed from authorities such as Bappebti, OJK, and Bank Indonesia to ensure that digital asset trading complies with Sharia principles and provides legal certainty for the Muslim community in Indonesia.   Keywords: Cryptocurrency, Bai’ as-sharf, Tokocrypto